1999
DOI: 10.1161/01.cir.100.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Chronic Heart Failure Hospitalizations and Mortality in France

Abstract: Clear seasonal variations in adult chronic heart failure hospitalizations and deaths were identified. The considerable economic impact on health care services warrants further epidemiological investigations and a more comprehensive approach to disease management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
113
3
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 28 publications
14
113
3
10
Order By: Relevance
“…Secondly, the study population was younger than in studies in the Northern Hemisphere. 1 Some of them found seasonality was more evident in elderly people 1,3 which was not corroborated in the present study, probably due to less marked seasonal climate changes.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Secondly, the study population was younger than in studies in the Northern Hemisphere. 1 Some of them found seasonality was more evident in elderly people 1,3 which was not corroborated in the present study, probably due to less marked seasonal climate changes.…”
Section: Discussioncontrasting
confidence: 89%
“…1,2 During winter months, hemodynamic changes are more accentuated and adverse events are triggered by low temperatures. 1 Recent studies have shown that cardiovascular tissues are the most sensitive to environmental chemicals and pollutants, 3 which can induce blood pressure changes, tissue infl ammation, autonomic imbalance, blood coagulation disorders, and heart rate variability and the ischemic threshold implicated in increased admissions for heart failure. 5 In tropical countries, as in Brazil, there are no studies on the seasonality of hospitalizations for heart failure.…”
Section: Descritoresmentioning
confidence: 99%
“…According to results of many studies levels of both clinic and ambulatory BP are on an average higher in winter season [9][10][11][12][13]. The highest level of cardiovascular mortality is also coincides with cold season [14][15][16][17][18][19][20]. This had been also confirmed by the studies performed at the National Medical Research Center for Preventive Medicine (NMRC PM) [19][20][21].…”
Section: Blood Pressure Phenotypes фенотипы артериального давленияmentioning
confidence: 76%
“…Согласно результатам мно-гих исследований уровень и клинического, и амбулаторного АД в зимний период в среднем выше [9][10][11][12][13]. Также имен-но в холодное время года отмечается наибольший уровень сердечно-сосудистой смертности [14][15][16][17][18][19][20]. Это подтвер-ждают и исследования, выполненные в НМИЦ ПМ [19][20][21].…”
Section: Blood Pressure Phenotypes фенотипы артериального давленияunclassified
“…Los estudios que se han ocupado del tema encuentran mayor tasa de ingresos en los meses invernales y lo atribuyen a factores tales como la mayor ingesta de sodio, episodios arrítmicos agudos, un incremento en la contaminación atmosférica o una superior incidencia de infecciones respiratorias, especialmente la gripe, en los meses fríos (22,23). Nuestro objetivo en este trabajo fue describir y comparar las variaciones estacionales de hospitalización y muerte por insuficiencia cardiaca crónica en la población rural y urbana atendida por nuestro hospital en Vigo.…”
Section: Introductionunclassified